2005
DOI: 10.1095/biolreprod.105.040824
|View full text |Cite
|
Sign up to set email alerts
|

Spermadhesin AQN1 Is a Candidate Receptor Molecule Involved in the Formation of the Oviductal Sperm Reservoir in the Pig1

Abstract: Sperm are stored in the isthmic region of the oviduct under conditions that maintain viability and suppress early capacitation steps until ovulation occurs. The initial contact between sperm and oviductal epithelium is mediated by carbohydrate-protein interactions. In the pig, the carbohydrate recognition system has been shown to involve oligomannosyl structures. The spermadhesins AWN and AQN1 are the dominant porcine carbohydrate-binding sperm proteins. The objective of this study was to demonstrate that AQN1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 74 publications
3
67
0
1
Order By: Relevance
“…involved in the establishment and maintenance of the oviductal sperm reservoir in mammals (Suarez 2002;Ekhlasi-Hundrieser et al 2005;Ignotz et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…involved in the establishment and maintenance of the oviductal sperm reservoir in mammals (Suarez 2002;Ekhlasi-Hundrieser et al 2005;Ignotz et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In a number of mammals, sperm are stored for several hours in an oviductal reservoir, in which sperm are bound tightly to the epithelium of the oviduct (e.g., Suarez and Osman 1987). Carbohydrates mediate the adherence of sperm to the epithelium, with different sugars playing important roles in different species (e.g., Demott et al 1995;Lefebvre et al 1995Lefebvre et al , 1997Ekhlasi-Hundrieser et al 2005). In cows, for example, biochemical studies suggest that fucose residues on oviductal annexins act as receptors for sperm, with several sperm-bound seminal proteins recognizing the fucose moiety (Ignotz et al 2001(Ignotz et al , 2007Gwathmey et al 2006).…”
mentioning
confidence: 99%
“…Boar spermadhesin AWN-1 is a sperm surface-associated lectin and a major protein of porcine seminal plasma (Calvete et al 1997). Recent studies have shown that boar spermadhesins AWN and AQN1 are the dominant carbohydrate-binding sperm proteins and AQN1 has been proposed as the molecule involved in the formation of the oviductal sperm reservoir (Ekhlasi-Hundrieser et al 2005). Binding of boar sperm to oviductal epithelium was inhibited by the addition of AQN1 but not by AWN (Ekhlasi-Hundrieser et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that boar spermadhesins AWN and AQN1 are the dominant carbohydrate-binding sperm proteins and AQN1 has been proposed as the molecule involved in the formation of the oviductal sperm reservoir (Ekhlasi-Hundrieser et al 2005). Binding of boar sperm to oviductal epithelium was inhibited by the addition of AQN1 but not by AWN (Ekhlasi-Hundrieser et al 2005). AQN1 recognizes both a-and b-linked galactose as well as Mana1-3 (Mana1-6)Man structures.…”
Section: Discussionmentioning
confidence: 99%
“…This process includes spermatozoa binding to oviductal epithelial cells via the plasma membrane overlying the acrosome (Gualtieri and Talevi, 2000) in a carbohydrate recognition dependent way (DeMott et al, 1995;Lefebvre et al, 1997;Suárez, 2001;Wagner et al, 2002). The sperm proteins that have been assigned a function in sperm reservoir formation are spermadhesins DQH (Manaskova et al, 2007) and AQN1 (Ekhlasi-Hundrieser et al, 2005) in pig; and PDC109 (BSPA1/A2), BSPA3, and BSP30K in bull (Gwathmey et al, 2006). The oviductal proteins that have been related to this process are annexins A1, 2, 4 and 5 in cow (Ignotz et al, 2007) and annexin A2 in pig (Teijeiro et al, 2009).…”
Section: Introductionmentioning
confidence: 99%